2021
DOI: 10.3389/fcell.2021.625715
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 Is a Novel Regulator of 20S Proteasome Subunits Expression and Activity

Abstract: Proteostasis collapses during aging resulting, among other things, in the accumulation of damaged and aggregated proteins. The proteasome is the main cellular proteolytic system and plays a fundamental role in the maintenance of protein homeostasis. Our previous work has demonstrated that senescence and aging are related to a decline in proteasome content and activities, while its activation extends lifespan in vitro and in vivo in various species. However, the mechanisms underlying this age-related decline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…When IIS is low, FoxO factors enter the nucleus to orchestrate the expression of pro-longevity genes, including the proteostasis network [45]. Recently, it has been shown that Foxo1 regulates the expression of the catalytic β5 subunit [13], and thus the increased FoxO1 transcriptional activity may account, at least partially, for the enhanced CT-L activity of cells treated with the composition. Simultaneously, SIRT1 plays a key role in lifespan and healthspan extension upon dietary restriction, regulates antioxidant cell response and contributes to telomere maintenance and genome integrity [25], and thus, the search for SIRT1 activators is one of the most extensive and robust topics of research [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When IIS is low, FoxO factors enter the nucleus to orchestrate the expression of pro-longevity genes, including the proteostasis network [45]. Recently, it has been shown that Foxo1 regulates the expression of the catalytic β5 subunit [13], and thus the increased FoxO1 transcriptional activity may account, at least partially, for the enhanced CT-L activity of cells treated with the composition. Simultaneously, SIRT1 plays a key role in lifespan and healthspan extension upon dietary restriction, regulates antioxidant cell response and contributes to telomere maintenance and genome integrity [25], and thus, the search for SIRT1 activators is one of the most extensive and robust topics of research [46].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, proteasome activation, either genetically or with natural compounds, enhances the lifespan of human cells [9], enhances stemness [10], alleviates the pathological phenotype of protein aggregation-related diseases and improves lifespan of model organisms [11,12]. In support of the eminent role of proteostasis in multiple aspects of cellular responses to environmental stimuli, we have established the regulatory role of the transcription factor FoxO1 on proteasome activity [13].…”
Section: Introductionmentioning
confidence: 94%
“…More specifically, although UPP upregulation was not always associated with foxo OE, increased UPP activity was a key feature of long-lived tissue-specific foxo overexpressing flies, further supporting the notion that the ability of the organism to maintain proteostasis correlates strongly with a delay in tissue aging. In support, it was shown that FOXO directly regulates the activity of 19S proteasome by upregulating the Rpn6 proteasome subunit, promoting resistance to various types of exogenous stressors [ 56 , 57 ]; also, FoxO1 was found to regulate both the expression and activity of the 20S proteasome by directly binding to the β5 proteasome gene’s promoter [ 58 ]. Further investigation in our study using genetic or pharmacological interventions revealed that proteasome activation in foxo overexpressing Drosophila lines is Nrf2/cncC-mediated.…”
Section: Discussionmentioning
confidence: 99%
“… Repair —FOXO targets include genes encoding proteins involved in repair of oxidative DNA and protein damage. For example, activity of the 20S proteasome is modulated by FOXO1, which controls transcription of the gene encoding the catalytic β5 subunit 51 . The 20S proteasome is a major contributor to cellular degradation of oxidized proteins 52,53 .…”
Section: Foxos In the Cellular Strategies Of Antioxidant Defensementioning
confidence: 99%